Nutritional status and eating attitudes of bariatric patients in the context of the Covid-19 pandemic in Brazil (Research, Society and Development, 2023)
The present study sought to test the association nutritional status and eating attitudes of bariatric patients in the context of the Covid-19 pandemic in Brazil. This is a cross-sectional, descriptive, analytical, online study, with 412 individuals, distributed in 21 Brazilian states, the study was carried out after approval by the Ethics Committee and contemplates female or male individuals, aged 18 years or over, who underwent bariatric surgery, and who accepted the research terms. Descriptive statistics (mean, standard deviation and frequency) were used. Pearson's chi-square test was applied to test the association between categorical variables, with analysis of adjusted residuals to identify which categories were associated. For all analyses, the statistical significance level of p